Long-Term Safety, Efficacy, and Quality of Life in Patients With Juvenile Idiopathic Arthritis Treated With Intravenous Abatacept for Up to Seven Years - Lovell, Daniel J.; Ruperto, Nicolino; Mouy, Richard; Paz, Eliana; Rubio-Perez, Nadina; Silva, Clovis A.; Abud-Mendoza, Carlos; Burgos-Vargas, Ruben; Gerloni, Valeria; Melo-Gomes, Jose A.; Saad-Magalhaes, Claudia [UNESP]; Chavez-Corrales, J.; et al. (Wiley-Blackwell, 2015)
Objective. The efficacy and safety of abatacept in patients with juvenile idiopathic arthritis (JIA) who experienced an inadequate response to disease-modifying anti-rheumatic drugs were previously established in a phase III study that included a 4-month open-label lead-in period, a 6-month double-blind withdrawal period, and a long-term extension (LTE) phase. The aim of this study was to present the safety, efficacy, and patient-reported outcomes of abatacept treatment (10 mg/kg every 4 weeks) during the LTE phase, for up to 7 years of followup. Methods. Patients enrolled in the phase III trial could enter the open-label LTE phase if they had not achieved a response to treatment at month 4 or if they had received abatacept or placebo during the doubleblind period. Results. One hundred fifty-three (80.5%) of 190 patients entered the LTE phase, and 69 patients (36.3%) completed it. The overall incidence rate (events per 100 patient-years) of adverse events decreased during the LTE phase (433.61 events during the short-term phase [combined lead-in and double-blind periods] versus 132.39 events during the LTE phase). Similar results were observed for serious adverse events (6.82 versus 5.60), serious infections (1.13 versus 1.72), malignancies (1.12 versus 0), and autoimmune events (2.26 versus 1.18). American College of Rheumatology (ACR) Pediatric 30 (Pedi 30) responses, Pedi 70 responses, and clinically inactive disease status were maintained throughout the LTE phase in patients who continued to receive therapy. Improvements in the Child Health Questionnaire physical and psychosocial summary scores were maintained over time. Conclusion. Long-term abatacept treatment for up to 7 years was associated with consistent safety, sustained efficacy, and quality-of-life benefits in patients with JIA.